Ethnology : an alternative in indigenous landscape planning and design - Mohamad, Sapura (Sapura Mohamad, 2010)
Physical development has jeopardized the traditional living environmetn of many Indigenous communities. Encroachment upon natural forest areas by major development for infrastructure, housing schemes and new townships has led to the dislocation of many indigenous communities from their original landscapes. Government resettlement and relocation initiatives and programs for indigenous communities, as a consequence of these landscape changes, have exposed indigenous communities to modern lifestyles and values that gradually impact upon their intrinsic cultural values in knowledge and practices, especially for young generations. This research paper reviews how ethnological knowledge may give invaluable insights into how environments influence or dictate Indigenous community responses and decision making for re-settlement. In addition, ethnographic approaches offer potential for use in landscape research methodologies to describe cultural realities. A quality understanding of Indigenous culture and community associations with environment will hopegully inform and contribute to the success and sustainability of landscape planning and development in these contexts